Pentraxin 3 in patients with severe sepsis or shock: the ALBIOS trial. (14th December 2016) - Caironi, Pietro; Masson, Serge; Mauri, Tommaso; Bottazzi, Barbara; Leone, Roberto; Magnoli, Michela; Barlera, Simona; Mamprin, Filippo; Fedele, Andrea; Mantovani, Alberto; Tognoni, Gianni; Pesenti, Antonio; et al.
Abstract: Background: The long pentraxin PTX3 is a key component of the humoral arm of innate immunity related to sepsis severity and mortality. We evaluated the clinical and prognostic significance of circulating PTX3 in the largest cohort ever reported of patients with severe sepsis or septic shock. Materials and methods: Plasma PTX3 was measured on days 1, 2 and 7 after randomization of 958 patients to albumin or crystalloids for fluid resuscitation in the multicentre Albumin Italian Outcome Sepsis (ALBIOS) trial. We tested the association of PTX3 and its changes over time with clinical severity, prevalent and incident organ dysfunctions, 90‐day mortality and treatment. Results: PTX3 was high at baseline (72 [33–186] ng/mL) and rose with the severity and number of organ dysfunctions ( P < 0·001) and the incidence of subsequent new failures. The PTX3 concentration dropped from day 1 to 7, but this decrease was less pronounced in patients with septic shock ( P = 0·0004). Higher concentrations of PTX3 on day 1 predicted incident organ dysfunctions. Albumin supplementation was associated with lower levels of PTX3 in patients with septic shock ( P = 0·005) but not in those without shock. In a fully adjusted multivariable model, PTX3 on day 7 predicted 90‐day mortality. Smaller drops in PTX3 predicted higher 90‐day mortality. Conclusions: In severe sepsis and septic shock, early high PTX3 predict subsequent new organ failures, while a smaller drop in circulating PTX3 over time predicts an increased risk of death. Patients with septic shock show lower levels of PTX3 when assigned to albumin than to crystalloids.